2014
DOI: 10.1007/s00192-013-2318-1
|View full text |Cite
|
Sign up to set email alerts
|

Prulifloxacin vs fosfomycin for prophylaxis in female patients with recurrent UTIs: a non-inferiority trial

Abstract: Both drugs provided adequate prophylaxis in patients with rUTIs, with no difference in efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Fosfomycin at 3 g every week was compared to prulifloxacin at 600 mg every week, for a total of 12 doses. At the end of 3 months, recurrent UTI occurred in 50% of patients receiving fosfomycin and 63% of patients in the prulifloxacin arm; 9 months later, the corresponding figures were 68% and 73%, respectively (257).…”
Section: Prophylaxismentioning
confidence: 94%
“…Fosfomycin at 3 g every week was compared to prulifloxacin at 600 mg every week, for a total of 12 doses. At the end of 3 months, recurrent UTI occurred in 50% of patients receiving fosfomycin and 63% of patients in the prulifloxacin arm; 9 months later, the corresponding figures were 68% and 73%, respectively (257).…”
Section: Prophylaxismentioning
confidence: 94%
“… 43 In this respect a more intensified dosing regimen would be justified. The results of a non-inferiority trial of Costantini et al 12 provide support for an intensified dosing regimen, as 3 g of fosfomycin every 7 days showed non-inferiority to prulifloxacin in female patients with rUTI. However, it is unknown if any unwanted effects occur with an intensified regimen, such as changes in intestinal microbiome, more side effects or development of resistance.…”
Section: Discussionmentioning
confidence: 94%
“…10 What remains unclear is the optimal dosing regimen of fosfomycin treatment in patients with rUTI, despite the numerous studies that have reported the pharmacokinetic and pharmacodynamic characteristics of fosfomycin, especially when administered IV for the treatment of various infections. 4,[11][12][13][14][15][16][17][18][19] Most of these studies lack accurate measurements of fosfomycin levels, especially in the lower range of clinically relevant concentrations. The recent development of LC-MS/MS to measure fosfomycin levels in serum and urine now allows an accurate analysis of fosfomycin in serum and urine of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies only included women, while 2 studies also allowed the inclusion of men [ 23 , 24 ]. The prophylaxis period was 6 months in 13/23 studies, 12 months in 9/23 studies, and 3 months in 1 study [ 25 ]. Of note, some studies suspended the prophylaxis as soon as there was a recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 9 HH trials [ 13 , 23 , 25 , 38–43 ] with 766 patients (636 with efficacy assessment) comparing different prophylactic antibiotics were included. Nitrofurantoin was the single most common comparator (to norfloxacin in 3 studies, to cefaclor in 1 study, and to trimethoprim [± sulfamethoxazole] in 3 studies); the pooled relative risk between nitrofurantoin and other comparator antibiotics indicated no significant difference (RR, 1.01; 95% CI, 0.74–1.37) ( Supplementary Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%